2019
DOI: 10.1109/lwc.2019.2912365
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Deep Learning at the Edge: A Novel Proactive and Cooperative Caching Framework for Mobile Edge Networks

Abstract: This letter proposes two novel proactive cooperative caching approaches using deep learning (DL) to predict users' content demand in a mobile edge caching network. In the first approach, a (central) content server takes responsibilities to collect information from all mobile edge nodes (MENs) in the network and then performs our proposed deep learning (DL) algorithm to predict the content demand for the whole network. However, such a centralized approach may disclose the private information because MENs have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…The main idea is to proactively transfer the content to be requested by a single of a cluster of UEs to the nearest possible BS/AP. Towards this direction, several researchers presented ML-based caching policies (Cheng et al, 2019;Jiang et al, 2019;Saputra et al, 2019;Wang X. et al, 2020;Kirilin et al, 2020;Ye et al, 2020). Specifically, in (Ye et al, 2020), the authors reported a device to primary and secondary BS clustering approach based on the requested content location in mmW ultra-dense wireless networks.…”
Section: Transport Layermentioning
confidence: 99%
“…The main idea is to proactively transfer the content to be requested by a single of a cluster of UEs to the nearest possible BS/AP. Towards this direction, several researchers presented ML-based caching policies (Cheng et al, 2019;Jiang et al, 2019;Saputra et al, 2019;Wang X. et al, 2020;Kirilin et al, 2020;Ye et al, 2020). Specifically, in (Ye et al, 2020), the authors reported a device to primary and secondary BS clustering approach based on the requested content location in mmW ultra-dense wireless networks.…”
Section: Transport Layermentioning
confidence: 99%
“…Popular preferences are then cached to improve the global cache hits. Saputra et al [30] have proposed two proactive and cooperative caching framework for mobile edge network. In the first approach, the edge nodes send data to a central server, which then creates a deep learning model based on the data popularity and sends it to the edge servers.…”
Section: Edge Caching Algorithmsmentioning
confidence: 99%
“…Besides, two popularity prediction algorithms are developed for two noise models. By using deep learning, authors in [11] proposed two proactive cooperative caching algorithms to predict user preferences in a centralized way and a distributed way, respectively. By learning user preference, two edge caching architectures are proposed to predict content popularity in [12].…”
Section: Related Workmentioning
confidence: 99%
“…Besides, cooperative caching [11], [18]- [22] is an effective approach to improve the utilization of storage resource. Researchers in [18] focused on a cooperative edge caching architecture for content-centric 5G networks, and proposed a mobility-aware caching framework for MUs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation